Follow-up study of Wiedemann-Rautenstrauch syndrome: Long-term survival and comparison with Rautenstrauch's patient G (2005)
BACKGROUND: Wiedemann-Rautenstrauch syndrome (WRS) characterizes a neonatal progeroid entity. In the last 30 years, 28 cases have been reported. In most cases of WRS, survival is short and long-term studies are impossible. CASE: In the present report, we describe a patient with WRS followed for 17 years at the Instituto de Genética, Universidad Nacional de Colombia; this is an exceptional survival period for a person with WRS. The information collected through 17 years for the present patient provides new knowledge about the natural evolution of this syndrome. New clinical and laboratory characteristics are compared with those reported for Rautenstrauch's patient 'G.' CONCLUSIONS: Our results confirm the variability of this syndrome, especially at the neurological level. However, many etiological and pathological aspects of this syndrome remain unknown. © 2005 Wiley-Liss, Inc.